Financial management and competitiveness in Lodging Establishments in the Junín Region - Castellanos-Meza, Stephany (2022)
The objective of determine the statistical conclusion between financial management and competitiveness in lodging establishments in the Junín region. The methodology used was a quantitative approach, basic type, correlational level and non-experimental design. To determine the population and sample, the non-probabilistic documentation was applied for convenience in order to be able to access it more easily. Questionnaires with polytomous answers and processing of these in Excel and SPSS were applied. As a result, a medium-low positive confirmation of 0.212, but statistically significant between the two variables, in terms of the dimensions of financial management and the competitiveness variable, relationships were obtained between low and high and equally statistically significant, thus verifying what was proposed in the research. Finally, it can be concluded that applying a certain use of financial management such as financial statements, use of accounting records, among others, affects competitiveness since this variable is carried out based on the human factor and the company's own resources, which generate the activities for your organization. According to the results obtained, among the most significant we have financial analysis and control, obtaining 70% and 76.7% of good management.